Coronary Heart Disease and Depression or Anxiety: A Bibliometric Analysis - Zhou, Yan; Zhu, Xue-Ping; Shi, Jing-Jing; Yuan, Guo-Zhen; Yao, Zi-Ang; Chu, Yu-Guang; Shi, Shuai; Jia, Qiu-Lei; Chen, Ting; Hu, Yuan-Hui (Frontiers in Psychology, 2021)
Coronary heart disease (CHD) often co-occurs with depression or anxiety and they often cause adverse impact on each other. Much research has been conducted in this field, but few bibliometric studies have been performed. We aimed to analyze pertinent publications over the past 17 years to acquire information about annual publication, authors, institutions and keywords and speculate future frontiers. Publications relating to CHD and depression or anxiety between 2004 and 2020 were identified from the Web of Science core collection (WOSCC) database. Bibliographic information, including authorship, country, citation frequency and interactive visualization were generated using VOSviewer1.6.16 and CiteSpace5.6.R5. In total, 8,073 articles relating to depressive or anxiety with CHD were identified in WOSCC database. The number of publications increased steadily despite occasional little drops. The USA, England, Germany, Canada and Netherlands ranked the top five productive countries. The top three journals were Psychosomatic Medicine, Journal of Psychosomatic Research and American Journal of Cardiology. The most productive authors were Denollet J. Pedersen SS. And Kivimaki M. The three hotspots of the research were “depression as an independent risk factor for CHD”, “depression and myocardial infarction” and “women take more risk in suffering depression after MI and get worse outcome”. We speculate that the top four future research frontiers are “treating depression in CHD patients with multimorbidity”, “psychometric properties of instruments for assessing depression and anxiety in CHD patients”, “depression or anxiety in post-PCI patients” and “other mental diseases in CHD patients”. Combined use of WOSCC database and practical analysis software CiteSpace and VOSviewer enabled robust bibliometric analysis of the literature about depression or anxiety and CHD published in the period 2004-2020. This study allows researchers to identify leading institutions and countries, determine research hotspots and get some hints from the speculated future frontiers.